2020
DOI: 10.18280/ts.370603
|View full text |Cite
|
Sign up to set email alerts
|

Video Data Extraction and Processing for Investigation of Vehicles’ Impact on the Asphalt Deformation Through the Prism of Computational Algorithms

Abstract: There are numerous algorithms and solutions for car or object detection as humanity is aiming towards the smart city solutions. Most solutions are based on counting, speed detection, traffic accidents and vehicle classification. The mentioned solutions are mostly based on high-quality videos, wide angles camera view, vehicles in motion, and are optimized for good visibility conditions intervals. A novelty of the proposed algorithm and solution is more accurate digital data extraction from video file sources ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 27 publications
(33 reference statements)
0
10
0
Order By: Relevance
“…This study analyzed the data with a backpropagation algorithm to determine the impact of traffic flow on asphalt deformation. Findings indicated that traffic flow significantly affected asphalt deformation, and the model had good accuracy in predicting the deformation [9,10]. Finally, references [11,12] studied the effects of vehicle speed on rutting deformation of asphalt pavement using real-time traffic data.…”
Section: Introduction To Asphalt Deformation and Lath And Nail Methodsmentioning
confidence: 98%
See 2 more Smart Citations
“…This study analyzed the data with a backpropagation algorithm to determine the impact of traffic flow on asphalt deformation. Findings indicated that traffic flow significantly affected asphalt deformation, and the model had good accuracy in predicting the deformation [9,10]. Finally, references [11,12] studied the effects of vehicle speed on rutting deformation of asphalt pavement using real-time traffic data.…”
Section: Introduction To Asphalt Deformation and Lath And Nail Methodsmentioning
confidence: 98%
“…First source is a video document source using road surveillance cameras with a 15-day period, which was used for sampling. A linear support vector machine model extracts vehicle number, class, speed, heading, and time from the recorded footage [10]. The weather and temperature factors are not considered as the measurements and modelling is performed on nearby lanes.…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…We consider block fading channel in this paper i.e., during each T, the channel remains static. Similar to [24][25][26], it is assumed that the wireless channel between the UAV and ground users is dominated by line of sight (LoS) link, hence the channels between the UAV and ground users are modelled by the free space path loss model. Thus, the channel power gain between the UAV and the mth user is denoted by h m ½n, given as:…”
Section: System Modelmentioning
confidence: 99%
“…At present, many computer vision systems are installed in outdoor environments and lowtemperature water environments. Their performance is easily affected by light distribution [18][19][20][21][22][23][24]. To complete different vision tasks, e.g., object detection, object recognition, and object retrieval, low-light images must be enhanced by different methods to achieve different processing effects.…”
Section: Introductionmentioning
confidence: 99%